Inovasi Media Pembelajaran Cerita Bergambar Berorientasi pada Literasi Dasar untuk Meningkatkan Prestasi Belajar Siswa - Khomsiyatun, Umi; Samiaji, Mukhamad Hamid (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to develop illustrated story learning media to develop early literacy in the learning of storytelling of second grade students. This research is a type of development research (R & D). In this study, six stages were used: (1) research and data collection, (2) planning, (3) development of product drafts (4) initial field trials, (5) revising the results of trials (6) field trials. The results obtained from this study are the needs of learning media according to students and teachers covering four aspects (a) understanding and need for teaching materials, (b) the need for teaching materials, (c) the need for physical teaching materials, and (d) needs towards the presentation and language of teaching materials. Data and analysis of the results of the expert validation assessment and Indonesian language teachers on the learning of pictorial stories. From expert I on average 84.8, the criteria is very good. From expert II on average 85.1, the criteria is very good. From the average user validator of 87.18, the criteria are very good. In general, the assessment of the feasibility of the learning media is very good. The results of product trials in the field obtained the average results of the experimental group's posttest score increased by 12 (from an average of 63.12 to 75.12. Keywords: Development, Learning Media, Picture Stories.